Determination of the Prevalence of Triazole Resistance in Environmental Aspergillus fumigatus Strains Isolated in South Wales, UK - Tsitsopoulou, Alexandra; Posso, Raquel; Vale, Lorna; Bebb, Scarlett; Johnson, Elizabeth; White, P. L. (Frontiers in Microbiology, 2018)
Background/Objectives: Azole resistance in Aspergillus fumigatus associated with the TR34/L98H mutations in the cyp51A gene have been increasingly reported. Determining the environmental resistance rate has been deemed important when considering front-line therapy for invasive aspergillosis. The aim of the study was to determine prevalence of azole resistance in environmental A. fumigatus isolates across South Wales. Methods: Over 5 months in 2015, 513 A. fumigatus isolates were cultured from 671 soil and 44 air samples and were screened for azole resistance using VIPcheck™ agar plates containing itraconazole, voriconazole and posaconazole. Resistance was confirmed by the CLSI M38-A2 methodology. The mechanism of resistance was investigated using the PathoNostics AsperGenius® Assay. Results: Screening by VIPcheck™ plate identified azole-resistance in 30 isolates, most of which (28/30) harbored the TR34/L98H mutation, generating a prevalence of 6.0%. Twenty-five isolates had a MIC of ≥2 mg/L with itraconazole, 23 isolates had a MIC of ≥2 mg/L with voriconazole and seven isolates had a MIC ≥0.25 mg/L with posaconazole. All isolates deemed resistant by VIPcheck™ plates were resistant to at least one azole by reference methodology. Conclusions: There is significant environmental azole resistance (6%) in South Wales, in close proximity to patients susceptible to aspergillosis. Given this environmental reservoir, azole resistance should be routinely screened for in clinical practice and environmental monitoring continued.